Assessment of health problems of sheep and goats based on ante-mortem and post-mortem inspection at Addis Ababa Abattoir, Ethiopia - Bekele Atoma, Tizeta; Szonyi, Barbara; Haile, Aklilu Feleke; Fries, Reinhard; Baumann, Maximillian P. O.; Randolph, Delia Grace (Frontiers in Veterinary Science, 2024)
Introduction Ethiopia has a rapidly growing small ruminant sector, which faces low productivity due to husbandry practices and poor health condition of the animals. A study was conducted in Ethiopia’s largest municipal abattoir with the objective to assess the health problems of sheep and goats presented for slaughter using standard ante-mortem and post-mortem methodology. Methods A cross-sectional study using systematic random sampling was conducted on 384 sheep and 384 goats from January to July 2014. Results Soiled skin (69.1%), poor body condition (24.3%), and nostril discharge (19.5%) were common among both species at ante-mortem examination. Gross lesions were frequent in livers (39.7%) and lungs (37.2%), while pneumonia (18.1%) and adhesions (13.8%) were frequent in the lungs of sheep and goats, indicating stress-related illness. Parasitic lesions, especially fasciolosis (19.3%) and hydatid cysts (8.1%) were significantly more common in sheep livers (p 0.05). The direct financial loss from lesions in both species was 1,077,015 ETB or 53,851 USD per year, most of which was estimated to occur from carcass bruising. Discussion The findings indicate that reducing parasite burden and preventing carcass bruising through improved handling could significantly increase the profitability of the small ruminant meat sector in Ethiopia.